Mucoepidermoid carcinoma of the salivary glands in Brazil: clinicopathological outcomes - Lucinei Roberto Oliveira; Danilo Figueiredo Soave; João Paulo Oliveira-Costa; Miguel Angel Sala Di Matteo; Alfredo Ribeiro-Silva
The biological features and clinical behavior of mucoepidermoid carcinomas are widely variable and poorly understood. This study aimed to investigate prognostic factors that may affect survival in patients with a primary diagnosis of head and neck mucoepidermoid carcinomas. The effects of age, gender, anatomic localization, tumor size, clinical stage, histological grade, recurrence, metastasis, compromised surgical margins and treatment on clinicopathological outcomes were investigated. Survival curves were generated using the Kaplan-Meier method and analyses were performed using the log rank test. A total of 16 cases were analyzed over a period of 18 years; males were 68.7 %, with ages ranging from 13 to 83 years. The 75 % of the tumors developed in the major salivary glands, 56.3 % in the parotid gland and they were predominantly classified as stage II 37.5 % and low-grade lesions 37.5 % at diagnosis. Surgical resection was performed in all patients. The follow-up period in this study ranged from 6 to 217 months. The 5 and 10-year overall survival rates were both 85.6 %. Disease-free survival rates were 81.8 % (5 years) and 68.2 % (10 years). There were statistically significant effects of tumor size (p= 0.05), metastasis (p= 0.04) and primary anatomic localization (p= 0.04) on disease-free survival rates. Through a long follow-up period in present study we could highlight the relevance of primary anatomical site, tumor size and metastasis as useful prognostic factors that may affect survival in patients with a primary diagnosis of head and neck mucoepidermoid carcinomas.